A COMPARISON OF THE EFFECTS OF LOCAL CORTICOSTEROID INJECTION AND PLATELET RICH PLASMA IN TREATING CHRONIC PLANTAR FASCIITIS - Suyog Rathi (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: A relatively prevalent degenerative condition that affects the backfoot is plantar fasciitis. In the past, local steroid injections were frequently utilised to treat chronic plantar fasciitis. Platelet-rich plasma (PRP) has been successfully used in recent years to treat persistent plantar fasciitis. Aims & objectives: The purpose of the current research was to assess and compare the efficacy of a single auto-logous platelet rich plasma (PRP) injection and steroid injection in individuals with persistent plantar fasciitis. Material and Methods: The current investigation was a single-center, prospective, comparative analysis that included patients 19 to 60 years old, of either gender, with heel pain that was most severe over the plantar aspect and that persisted for more than six months. Patients were randomised into two groups at random: group PRP had a PRP injection, while group steroids received a combination of 1 mL local anaesthetic and 2 mL methylprednisolone. Results: In the current research, 200 patients were allocated into two groups at random: PRP (n = 100) and steroid (n = 100). The majority was female and in the age range of 41 to 50. Age and sexual orientation were comparable between the two groups, and the difference was statistically insignificant. For both groups, the VAS score was computed at baseline, 1, 3, and 6 months. Baseline VAS scores were comparable, and the statistical difference between them was not large. At 1, 3, and 6 months, VAS scores were higher in the PRP group compared to the steroid group, and the difference was statistically significant (p 0.05). Mean AOFAS scores were comparable between the two groups at baseline and after one month, and the difference was not statistically significant (p>0.05). At 3 and 6 months, the mean AOFAS score was higher in the PRP group compared to the steroid group, and the difference was statistically significant (p 0.05). Conclusion: When symptom relief is desired 3 and 6 months after the initial injection for the treatment of PF, platelet rich plasma (PRP) is superior to corticosteroid injection. Keywords: chronic planter fasciitis, platelet rich plasma (PRP), corticosteroid, VAS for heel pain.